En busca de Catalina de Erauso identidades en conflicto en la vida de la monja alférez - Mendieta, Eva (Col·lecció "Sendes", 2010)
An investigation of the life and historical milieu of Catalina de Erauso (1592-1650), the lieutenant nun, with emphasis on her national and gender identities.